TURISMEMORFOSIS SEBAGAI PERKEMBANGAN PARIWISATA DI BADUNG, BANYUWANGI DAN LUWU TIMUR - Mahagangga, I.G.A.O.; Anom, I Putu; Kusuma Negara, I Made (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021)DO - 10.24843/IPTA.2021.v09.i01.p09, 2021)
The tourism development in many tourism destination appears to ignore history. Geneology or social record as a history of the formation of existing conditions is considered less important. This study try to understand by apply the tourimsmorphosis concept in Badung, Banyuwangi and East Luwu. Tourismmorphosis as the evolution of tourism can be both progress and regress as an inevitable change. Consisting of the introductory stage, the reaction stage, the institutionalization stage and the compromise stage. The research paradigm is qualitative with qualitative methods and techniques, hermeneutic data analysis techniques and thick descriptive data presentation. The research results understanding that Badung was at the compromise stage, Banyuwangi at the institutional stage and East Luwu at the introductory stage. Hence, the consider of research findings could be used as a basis for future tourism development.